Learning technologies and user interaction : diversifying implementation in curriculum, instruction, and professional development - Seo, Kay Kyeong-Ju; Gibbons, Scott (New york: Routledge, 2022)
"Learning Technologies and User Interaction explores the complex interplay between educational technologies and those who rely on them to construct knowledge and develop skills. As learning and training continue to move onto digital platforms, tools such as artificial intelligence, predictive analytics, video games, virtual reality, and more hold considerable potential to foster advanced forms of synergy across contexts. Showcasing a variety of contributors who are attuned to today's networked technologies, environments, and learning dynamics, this book is ideal for students and scholars of educational technology, instructional design, professional development, and research methods"--
Contributor biographies -- Introduction -- Chapter 1: interaction and the role of technology / by Scott Gibbons and Kay K. Seo / Unit I: enriching curriculum -- Chapter 2: learning analytics to support student interaction and learning design: initial report on a human-centered prototype design / by Priya Sharma, Mahir Akgun, and Qiyuan Li -- Chapter 3: assessing the impact of immersive virtual reality on objective learning outcomes based on presence, immersion, and interactivity: a thematic review / by Hui-Ching Kayla Hsu and Cong Wang -- Chapter 4: beyond information acquisition: a critical design framework to support emancipatory discourses and thinking in a transmedia learning experience / by Scott J. Warren, Meranda M. Roy, and Heather A. Robinson -- Unit II: diversifying instruction -- Chapter 5: oral interaction in technology education / by Wendy Fox-Turnbull -- Chapter 6: using sound to enhance interactions in an online learning environment / by Yun Li and Sherman Finch -- Chapter 7: from online interaction to social learning analytics and community building: a learning engineering perspective / by Chih-Hsiung Tu, Cherng-Jyh Yen, Emre Ozkeskin, and Laura Sujo-Montes -- Unit III. revamping professionalism -- Chapter 8: virtual reality as participant: instructional design considerations for an introduction to flying course / by Kim A. Hosler -- Chapter 9: learning technology in the secondary classroom / by Chastity Rohan and Corey Duzan -- Chapter 10: remote learning and the democratization of the student-teacher relationship / by Larissa Pahomov.
Includes bibliographical references.
Keywords: Educational technology; Computer-assisted instruction; Computer-assisted instruction; Career development